MERCHANDISE DESIGN AS PT RADIO CHANDRA TARUNA PROMOTION - Trifandianto, Ivan (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
Radio is one of the information media that is a daily food by the community. The existence of radio in people's lives certainly cannot be separated from the function of radio as a medium of information and for entertainment. In Semarang, there are a lot of private radios present to entertain entertainment and information, one of them is Chandra Taruna Radio (RCT FM) which is a seasoned radio in Semarang City. This radio is in the Bukitsari Region, Banyumanik, Semarang. In Semarang there are a lot of radio competitors who are competitors of Radio Chandra Taruna (RCT FM) itself. So there needs to be an effort, to build a corporate image and listener loyalty so that listeners can faithfully listen to RCT FM and attract potential advertisers on this radio. The aim of this study project is to produce a merchandise design, which illustrates the elements of the merchandise design that illustrates the role of RCT FM as a radio that provides information and entertainment. So that it can increase the attractiveness of prospective listeners and prospective advertisers and increase the loyalty of old listeners. The process of designing merchandise through several stages of the process of creating the sequence of pre-production processes, production processes, and post-production processes. The results of the design of merchandise PT. Radio Chandra Taruna based on its type namely, in the form of t-shirts, tote bags, tumblers, notebooks, mugs, hand fans, and key chains. With the design of this merchandise is expected to help PT. Radio Chandra Taruna built its self-image to the audience, added value, and made PT. Radio Chandra Taruna can compete with its competitors